An unusual distribution of supplemental teeth in the primary dentition - A. ROBERTS, S. T. BARLOW, M. M. COLLARD & M. L. HUNTER (Paediatric Dentistry, 2005)
Supernumerary teeth are more common in the permanent than the primary dentition [1].